ევრიპიდეს ტრაგედიის “იფიგენია ავლისში” კინემატოგრაფიული ტრანსკოდიფიცირების ძირითადი პრინციპები იორღოს ლანთიმოსის ფილმში “წმინდა ირმის მკვლელობა” - ცანავა ანნა (ლოგოსი, 2023)
The article refers to the cinematographic adaptation, so-called “transcodification”, of ancient Greek tragedy in the example of Yorgos Lanthimos's film "The Killing of a Sacred Deer"(2017). The latter is the cinema reception of Euripides' tragedy "Iphigenia in Aulis". The article aims to show and analyze the main cinematographic means and strategies through which the director transfers Euripides' text into a visual medium. In this regard, two levels of trascodification are distinguished: narrative and visual. At the level of the narrative structure, the film transformation of the original text involves the substitution of the setting, characters, and plot events of the tragedy with completely different, but essentially identical, elements familiar to modern society. The visual level of transcodification involves the reconstruction of the main worldview and emotional aspects of the Euripidean tragedy through visual signs and camera movement. The combination of the above-mentioned two aspects allows the director to convey accurately and adequately the literary original to the target 21-century audience that is unfamiliar with the aesthetics of ancient Greek drama.